Improved Solid-Contact Nitrate Ion Selective Electrodes Based on Multi-Walled Carbon Nanotubes (MWCNTs) as an Ion-to-Electron Transducer - S. M. Hassan, Saad (Sensors (Basel), 2019)
Possible improvement of the performance characteristics, reliability and selectivity of solid-contact nitrate ion-selective electrodes (ISE) (SC/NO(3)(−)-ISE) is attained by the application of a nitron-nitrate (Nit(+)/NO(3)(−)) ion association complex and inserting multi-walled carbon nanotubes (MWCNTs) as an ion-to-electron transducer between the ion sensing membrane (ISM) and the electronic conductor glassy carbon (GC) substrate. The potentiometric performance of the proposed electrode revealed a Nernstian slope −55.1 ± 2.1 (r² = 0.997) mV/decade in the range from 8.0 × 10(−8)–1 × 10(−2) M with a detection limit of 2.8 × 10(−8) (1.7 ng/mL). Selectivity, repeatability and reproducibility of the proposed sensors were considerably improved as compared to the coated disc electrode (GC/NO(3)(−)-ISE) without insertion of a MWCNT layer. Short-term potential stability and capacitance of the proposed sensors were tested using a current-reversal chronopotentiometric technique. The potential drift in presence of a MWCNT layer decreased from 167 μVs(−1) (i.e., in absence of MWCNTs) to 16.6 μVs(−1). In addition, the capacitance was enhanced from 5.99 μF (in absence of MWCNTs) to 60.3 μF (in the presence of MWCNTs). The presented electrodes were successfully applied for nitrate determination in real samples with good accuracy.